Understanding gene interactions controlling resistance to pepper yellow leaf curl disease through phenotype-based analysis - Tri Wahono Dyah Ayu Sayekti; Muhamad Syukur; Sri Hendrastuti Hidayat; Sobir Sobir; Awang Maharijaya (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2025)
Pepper yellow leaf curl disease (PYLCD) is the primary disease that affects chili plants, resulting in a loss of quality and quantity. The identification of chili plants resistant to PYLCD is a solution to support optimal chili cultivation. The purpose of this study was to estimate genetic parameters to obtain information on the genetic control of chili resistance to PYLCD. The genotypes used in this study consisted of four parental, four hybrid genotypes, and 180 individuals of the F2 population. The results showed that the genotypes "F6074" and "IPBC12" were categorized as resistant, while the genotypes “IPBC5” and “YUNI” were categorized as susceptible. The distribution of resistance level in chili peppers to yellow curly leaf disease tends to follow a ratio of 13:3, with a dominance of susceptible traits. The assumption for this phenomenon is that resistance to PYLCD is controlled by at least two genes. Both genes have dominant and recessive epistatic interactions. Keywords: Begomovirus; chi-square; epistasis; resilience